Evaluation of Snake Gourd (Trichasanthes Anguina L) Test Hybrids Comparing with Four Popular Checks - Haque, M.M.; Uddin, M. S.; Mehraj, H.; Uddin, AFM Jamal (International Journal of Applied Sciences and Biotechnology, 2014)
An experiment was conducted at Research and Development (Vegetable) Farm, Supreme Seed Company Limited, Mymensingh in 20th March to 14th June, 2013 to evaluate performance of eight snake gourd genotypes. Among snake gourd genotypes four were test hybrid viz. SG1001, SG1002, SG1003 and SG1004 (from the seven inbreed lines) and four were checks (three from local market and one from BADC) viz. SUPREMA, RUNNER, SURMA, ZUM LONG. Wide ranges of variability were found in the studied characters among the genotypes. Maximum total number of fruits was found from SUPREMA (235.3/plot) which was statistically similar to RUNNER (201.3/plot) while minimum from ZUM LONG (24.7/plot) that was used as check. SG1002 genotype provided maximum marketable yield (49.6 kg/plot) and minimum from ZUM LONG (30.7 kg/plot). SUPREMA, SG1002, SG1001 and RUNNER genotypes showed better performance in respect of number of fruits/plant, fruit length, individual fruit weight, yield/plot and some other characters. Flowering period was significantly correlated with yield contributing characters. Number of fruits/plant, total number of fruits/plot and individual fruit weight was significantly positively correlated with yield of snake gourd. DOI: http://dx.doi.org/10.3126/ijasbt.v2i4.11302 Int J Appl Sci Biotechnol, Vol. 2(4): 525-528